2000
DOI: 10.1116/1.1288137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of titanium oxide films grown on bare glass and boiled glass in 50% H2SO4 by metal-organic chemical vapor deposition

Abstract: Titanium oxide films were deposited on bare glass and boiled glass in 50% H2SO4 for 30 min at various substrate temperatures by metal-organic chemical vapor deposition. We investigated the effects of a substrate temperature between 300 and 550 °C on such properties as thermal stability, deposition rate, and chemical states of the films. The thickness of the films is independent of the substrate treatments. The deposition rate of the films is linearly decreased with increasing substrate temperature. Rutherford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It can also be expected that a reduction in surface sodium concentration might enhance coordination with other metal constituents in glass. Lee and Condrate found that more stable carboxylate species can form when Al, Ca, and Mg are present (32)(33)(34)(35). The asymmetric CO 2 stretching mode for carboxylic acids adsorbed on alumina and oxidized aluminum surfaces has been reported in the 1583-1608 cm -1 region (32,(36)(37)(38).…”
Section: Adsorption On Acid Leached Sodium Aluminoborosilicate Fibers...mentioning
confidence: 99%
“…It can also be expected that a reduction in surface sodium concentration might enhance coordination with other metal constituents in glass. Lee and Condrate found that more stable carboxylate species can form when Al, Ca, and Mg are present (32)(33)(34)(35). The asymmetric CO 2 stretching mode for carboxylic acids adsorbed on alumina and oxidized aluminum surfaces has been reported in the 1583-1608 cm -1 region (32,(36)(37)(38).…”
Section: Adsorption On Acid Leached Sodium Aluminoborosilicate Fibers...mentioning
confidence: 99%